Analisis Poros Roda Depan Sepeda Motor Vespa PX - Mohamad Rifal Darojat; Iwan Nugraha Gusniar; Iman Dirja (Jurnal Ilmiah Wahana Pendidikan, 2023)
The front wheels are used to hold the load and maintain the balance of the vehicle while walking. The front axle must be of sufficient dimensions to support the loads imposed on it. This design aims to make an axle using the appropriate material so that it is safe to use, then the method used is to measure directly on the vehicle taking into account the specifications of the vehicle and also the specifications of the axle. The material used to design the wheel axle with bending load is S45C construction steel with a tensile strength of 490-550 MPa. The shaft that receives the bending load produces a stress that occurs due to the shaft of 105 MPa and a permissible diameter of 57 mm while the safety factor that occurs in the calculation of the front axle is 4.2, an element of the machine will be SAFE, if: Material Strength > Occurring Stress. From the calculation results it is also known that the deflection that occurs on the shaft is 7.7 mm.